Self-Reported Use of HIV Preexposure Prophylaxis Is Highly Accurate Among Sexual Health Clinic Patients in New York City. Issue 11 (10th November 2022) - Qasmieh, Saba; Nash, Denis; Gandhi, Monica; Rozen, Elliot; Okochi, Hideaki; Goldstein, Harris; Herold, Betsy C.; Jamison, Kelly; Pathela, Preeti
Abstract : Compared with an objective biomarker of drug-level measurements, self-report provides an accurate indicator for assessing preexposure prophylaxis use among New York City sexually transmitted infection clinic patients. Abstract: In New York City, 91% of sexually transmitted infection clinic patients reported preexposure prophylaxis (PrEP) use that matched the detection of PrEP in their serum. Self-report had 80% sensitivity and 96% specificity ( κ = 0.79) compared with measured PrEP. Our findings suggest that self-report may be a valid indicator of PrEP uptake.